Life quality of the Russian population by the data from ESSE-RF study - A. V. Kontsevaya; S. A. Shalnova; Yu. A. Balanova; A. D. Deev; M. V. Sherashova; S. A. Boytsov; I. A. Trubacheva; D. V. Duplyakov; D. S. Kaskaeva; E. N. Shmatova; A. A. Kosinova; R. R. Ruf; et al. (Кардиоваскулярная терапия и профилактика, 2016)
Life quality (LQ) is an integrated parameter of the health, applied for integral characterization of population health, and as the parameter of healthcare interventions effectiveness.Aim. To assess LQ in Russian population at the age 25-64 y. o. in general and in various socio-economical groups using EQ-5D, by the results of ESSE-RF (2012-2013) study.Material and methods. LQ was assessed on representative selections of inhabitants of 13 Russian Federation regions, aged 25-64 (males 8327, females 13497) with response 80%. LQ was assessed via international questionnaire EUROQOL — EQ-5D: 1) no decline; 2) mild decline; 3) significant decline; scoring also performed with visualanalogue scale (VAS). Integral LQ by EUROQOL performed with Shaw JW et al. method (ranging from 0,0 (death) to 1,0 (perfect health)).Result. EQ-5D index of Russian population was 0,87 with no gender difference. By the increase of the age LQ declines. Educational gradient of LQ was significant only in VAS (p<0,05). Wealth level negatively associated with LQ. Most common (p<0,0005) were disorders by the components pain/discomfort and anxiety/depression. Part of those with lower LQ among males is lesser than in females, by all 5 factors of the LQ, and in all educational states. Regional specifics of LQ by EQ-5D index: from 0,82 in Vladikcaucas to 0,95 in Orenburg (p<0,0005). There was significant correlation of EQ-5D index with unemployment level (0,4) and consumer prices index (0,29) in regions.Conclusion. Monitoring of LQ is necessary condition for assessment of efficacy of population health improvement interventions, and the LQ values obtained will be useful as populational norms for health condition assessment in addition to morbidity and mortality factors.